Overuse of Steroid Drugs Methylprednisolone and Dexamethasone (Oral) Causes a Diabetic Patient to Become Infected with the Black Fungus in the Corona Virus. (Global Journal of Medical Research, 2021)
Abstract not found
Keywords: methylprednisolone; dexamethasone; side effect; drug interaction; diabetes patients; black fungus; eye diseases etc